2017
DOI: 10.1111/ijd.13601
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis suppurativa gains increasing interest on World Wide Web: a source for patient information?

Abstract: In addition to an increasing interest, we found a broad variation in the quality, readability, popularity, and timeliness of content on HS-related websites. Improvement of the quality and readability of HS-related websites is desirable to potentially raise disease awareness and contribute to an earlier presentation of patients suffering with undiagnosed HS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Google Trends® is a free tool provided by Google Inc that is easily accessible to the public to analyze search volumes according to user‐defined search terms with data on geographical and temporal trends. In Dermatology, these trends have been analyzed to assess public interest in skin diseases, dermatitis, esthetic plastic surgery, skin cancer, Mohs micrographic surgery, sunscreen, tanning, and hidradenitis suppurativa …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Google Trends® is a free tool provided by Google Inc that is easily accessible to the public to analyze search volumes according to user‐defined search terms with data on geographical and temporal trends. In Dermatology, these trends have been analyzed to assess public interest in skin diseases, dermatitis, esthetic plastic surgery, skin cancer, Mohs micrographic surgery, sunscreen, tanning, and hidradenitis suppurativa …”
Section: Introductionmentioning
confidence: 99%
“…In Dermatology, these trends have been analyzed to assess public interest in skin diseases, dermatitis, esthetic plastic surgery, skin cancer, Mohs micrographic surgery, sunscreen, tanning, and hidradenitis suppurativa. [6][7][8][9][10][11][12][13][14][15][16] The worldwide search interest in "sunscreen" has been generally increasing since 2008 with a waning trend for the search term "tanning bed." 15 In the United States of America, Google Trends® found that melanoma incidence was positively associated with searches for "sunscreen" and "sunburn" and negatively associated with "skin cancer" searches.…”
Section: Introductionmentioning
confidence: 99%
“…Hessam S, Salem J, Bechara FG, Haferkamp A, Heidenreich A, Paffenholz P, Sand M, Tsaur I, Borgmann H. Hidradenitis suppurativa gains increasing interest on World Wide Web: a source for patient information? Int J Dermatol; 2017 [28] A strong positive association between the UV index and SVI for sunburn-related terms was demonstrated. This suggests tracking search terms for sun protective measures as an indication of public awareness and efficacy of public health programs.…”
Section: Worldwidementioning
confidence: 93%
“…Internet and PubMed searches for HS are also rising, suggesting burgeoning public and scientific interest. 1 Some authors postulate publication productivity is a surrogate for scientific maturation and achievement. 2 For example, research in psoriasis grew rapidly between 1993 and 2007, facilitating substantial increases in high-quality publications, disease understanding and therapeutic options.…”
Section: Introductionmentioning
confidence: 99%
“…Publication numbers have grown from ~15 publications annually (1990–2000) to nearly 300 in 2018. Internet and PubMed searches for HS are also rising, suggesting burgeoning public and scientific interest . Some authors postulate publication productivity is a surrogate for scientific maturation and achievement .…”
Section: Introductionmentioning
confidence: 99%